Alternatives for issuer-paid credit rating agencies - Dion Bongaerts (European Central Bank (ECB), 2014)
This paper investigates the economic viability and welfare contribution of alternatives to issuer-paid credit rating agencies (CRAs). To this end, it introduces a heterogeneous competition model for credit and ratings markets. Frictions among issuers or investors induce rating inflation from issuer-paid CRAs. Investor-paid CRAs suffer from three sources of free-riding and are generally not economically viable when competing with issuer-paid CRAs. Only for very limited parameter ranges can investor-paid CRAs thrive and counter rating inflation. Other proposed alternatives such as investor-produced ratings and CRA co-investments employ skin-in-the-game to induce proper screening accuracy. However, as traditional issuer-paid CRAs can cater better to issuers, such alternatives generate little demand or are implemented ineffectively. Hence, this paper provides an explanation for the evolution, dominance and resiliency of issuer-paid CRAs.
Keywords: G24; G28; L14; 330; competition; credit rating agencies; regulation; reputation